Design, knowledge and human interest*. Issue 2 (3rd July 2017) - Dilnot, Clive
Abstract: This paper is an analytically orientated attempt to reshape understanding of the connections of theory (in the wide sense) and design. It does so by building on Habermas' double reconstruction of the interrelation of knowledge and human interests and the necessity of reflection in order to show that today, even in limited ways, design is a necessary form of theoretical, and not only practical, reflection. The underlying premise here is that in an epoch of the artificial, design is objectively situated to offer a distinctive mode of thinking concerning how we contend with the world as now is, i.e. the world we have made.